The salt fix : why the experts got it all wrong--and how eating more might save your life - DiNicolantonio, James (Harmony, 2017)
"We all know the dangers of sugar and salt: but the danger attributed to the second white crystal has more to do with getting too little of it, not too much. A leading cardiovascular research scientist and doctor of pharmacy overturns conventional thinking about salt and explores instead the little-understood importance of it, the health dangers of having too little, and how salt can actually help you improve sports performance, crush sugar cravings, and stave off common chronic illnesses. Too little salt in the diet can shift the body into semi-starvation mode and cause insulin resistance, and may even cause you to absorb twice as much fat for every gram you consume. Too little salt in certain populations can actually increase blood pressure, as well as resting heart rate. We need salt in order to hydrate and nourish our cells, transmit nerve signals, contract our muscles, ensure proper digestion and breathing, and maintain proper heart function. The Salt Fix will show how we wrongly demonized this essential micronutrient as well as explain what the current science really says about this misunderstood mineral and how to maximize its effect so you can enjoy ideal health and longevity"--